Genetic parameters for linear type traits in the Rendena dual‐purpose breed. (26th August 2013) - Mazza, S.; Guzzo, N.; Sartori, C.; Berry, D.P.; Mantovani, R.
Summary The aim of the study was to estimate the genetic parameters for five composite traits and 20 individual type traits on 10 735 first‐parity Rendena dual‐purpose cows. Fixed effects included in the linear animal mixed models were herd‐year‐classifier, days in milk and age at first calving; the additive genetic effect of the animal was included as a random effect. Heritability estimates varied from 0.12 (feet) to 0.52 (stature). Genetic correlations between the individual body size traits were all ≥0.69; similar strong genetic correlations existed between traits describing similar morphological characteristics (e.g. mammary system, fleshiness). Many of the body size traits were negatively genetically correlated with animal fleshiness. Genetic trends showed that genetic merit for body size increased consistently over the last 10 years, while genetic merit for fleshiness declined. These results suggest that the characteristics of the dual‐purpose Rendena cattle are becoming more like specialized milk‐producing animals. Nonetheless, sufficient genetic variation exists to halt or reverse the deterioration in fleshiness.